PENGARUH KERAGAMAN MENU, KEPERCAYAAN DAN NILAI PELANGGAN TERHADAP LOYALITAS PELANGGAN DENGAN KEPUASAN SEBAGAI VARIABEL MEDIASI - Untung Sriwidodo, Yohana Angel Chrestina, Marjam Desma Rahadhini & (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2017)
This study aimed to analyze the effect of the diversity of the menu, trust andcustomer value on customer satisfaction and loyalty, and satisfaction mediates the effectof the diversity of the menu, trust and customer value on customer loyalty. This studyuses primary and secondary data. The sampling technique used purposive sampling.Data were analyzed using analysis of Structural Equation Modeling (SEM) wiht IMBsoftware SPSS Amos 20. The results of the analysis obtained significant influence thediversity of the menu and the value of the customer to customer satisfaction, there is nosignificant effect of trust to customer satisfaction, a significant influence satisfactioncustomer loyalty, there is a signifacant effect on loyalty diversity of the menu, there is nosignificant effect on the value of customer loyalty, satisfaction mediates the effect of thediversity of the menu and truston customer loyalty, satisfaction does not mediate theeffect of customer value on costumer loyalty.Keywords: diversity menu, trust, costumer value, satisfaction, customer loyalty.